History between Red Brackets: The Cold War in History Museums around the Baltic Sea. Issue 1 (1st July 2019) - Hegardt, Johan
Abstract : This article derives from the research project entitled "Art, Culture and Conflict: Transformations of Museums and Memory Culture around the Baltic Sea after 1989, " which was financed by the Foundation for Baltic and East European Studies, Södertörn University. It discusses how history museums in Finland, Sweden, Estonia, Latvia, and Lithuania have reacted to the fall of the Iron Curtain and the conclusion of the Soviet occupation of the three Baltic states. It argues that the Cold War is understood by the museums as a special historical epoch not comparable to any other historical period in these six countries. It concludes that to be able to deal with this particular point in history we either need to metaphorically put the Cold War in between red brackets, as it were, which makes it possible to address the Cold War when needed, or to place it outside the historical narrative of the modern rise of the five discussed nation-states.